Application of Generalized Autoregressive Conditional Heteroschedasticity Model on Inflation and Share Price Movement in Nigeria - Manasseh, Charles O.; Omeje, Ambrose N. (International Journal of Economics and Financial Issues, 2016)
In the past, studies on the linkage between share prices movement and inflation has been subjected to extensive research by academics, researchers, practitioners and policy makers since the 1990s. Most studies in the industrialized economies showed the existence of negative relationship between share price movement and inflation. Consequently, this paper utilized GARCH model and investigated the influence of inflation on share price movement in Nigerian stock market, using quarterly data for the period 1981 to 2012. The findings of this paper suggest that the GARCH terms of the share price movement in Nigeria depicted a variance of autoregressive conditional heteroscedastic behaviour. Furthermore, share price movement and inflation exhibited a collective volatility of about 0.0015% during the study period. Share price movement exhibit a volatile shock of about 79% in behaviour while a 1% increase in inflation leads to about 0.15% decrease in share price movement in Nigeria. In addition, a 1% increase in market capitalization leads to about 66.8% increase in share price movement in Nigeria. Therefore, stabilizing inflation will deepen the Nigerian stock market the more thereby leading to a trickling down effect on the stock market capitalization. Hence, policies geared towards the reduction and stabilization of inflation to at least, single digit is recommended to the Nigerian monetary authorities. Keywords: Inflation, Share Price, GARCH, Influence, Stock Market. JEL Classifications: E31, G00, G10, G12